Signing dissent in the name of “woman ”: Reflections on female activist coalitions in Istanbul, Turkey - Avramopoulou, Eirini (The Greek Review of Social Research, 2013)
This paper focuses on the unexpected female coalition created in 2008 between feminist, LBT (lesbian, bisexual, transsexual) and religious activists in Turkey, and asks how women come to signify –and possibly challenge– the pre-established demarcations of politics framing gendered precariousness. How do women claim to sign differently the contract of the political? By referring to the neoliberal and conservative values of the current government’s agenda and underlying the importance of newly formed alliances between activist women, it explores the complex ways in which these three groups struggle to be heard within public debate in Turkish society and how they try to form alliances despite their differences.